Gut symbiotic bacteria enhance reproduction in Spodoptera frugiperda (J.E. Smith) by regulating juvenile hormone III and 20-hydroxyecdysone pathways - Bo Chu; Shishuai Ge; Wei He; Xiaoting Sun; Jiajie Ma; Xianming Yang; Chunyang Lv; Pengjun Xu; Xincheng Zhao; Kongming Wu (Microbiome)
Abstract Background The insect gut microbiota forms a complex, multifunctional system that significantly affects phenotypic traits linked to environmental adaptation. Strong reproductive potential underpins the migratory success, population growth and destructive impact of the fall armyworm, Spodoptera frugiperda (J.E. Smith). However, the precise role of gut bacteria in S. frugiperda reproductive processes, distribution and transmission dynamics remains unclear. Results We examined the gut microbiota of S. frugiperda a major invasive agricultural pest, identifying Enterococcus, Enterobacter, and Klebsiella as core microorganisms present throughout its life cycle. These microbes showed heightened activity during the egg stage, early larval stages and pre-oviposition period in females. Using an axenic insect re-infection system, Enterococcus quebecensis FAW181, Klebsiella michiganensis FAW071 and Enterobacter hormaechei FAW049 were found to significantly enhance host fecundity, increasing egg production by 62.73%, 59.95%, and 56.71%, respectively. Metagenomic and haemolymph metabolomic analyses revealed a positive correlation between gut symbiotic bacteria and hormone metabolism in female S. frugiperda. Further analysis of metabolites in the insect hormone biosynthesis pathway, along with exogenous injection of juvenile hormone III and 20-hydroxyecdysone, revealed that gut microbes regulate these hormones, maintaining levels equivalent to those in control insects. This regulation supports improved fecundity in S. frugiperda, aiding rapid colonization and population expansion. Conclusions These findings emphasize the pivotal role of gut bacteria E. quebecensis FAW181, E. hormaechei FAW049, and K. michiganensis FAW071 in enhancing S. frugiperda reproduction by modulating JH III levels through JHAMT regulation and concurrently modulating the levels of 20E and its precursors via PHM. Our results provide novel insights into microbe–host symbiosis and pest management strategies for alien invasive species. Video Abstract